Improving the Outcomes of Breast Cancer in China: Physicians’ Beliefs, Recommendations, and Practices for Breast Cancer Screening - Wu, Tsu-Yin; Raghunathan, Vedhika; Shi, Jianguo; Hua, Wang; Yu, Wang; Deng, Abby (Asian Pacific Journal of Cancer Care, 2020)
Objective: Physicians play a key role in performing and referring patients for cancer screening. A paucity of data exists for breast cancer screening (BCS) recommendations, demographic characteristics, screening practices, and barriers of screening among physicians. The purpose of this project is to examine physicians’ characteristics, practices, and beliefs about BCS recommendations and its barriers. Methods: The study used a descriptive correlational design and 110 surveys were completed. Data was analyzed using descriptive and inferential statistics generated with Statistical Packages for Sciences (SPSS) 26.0 version. Results: Most of the surveyed Chinese physicians worked in the community, were females, and between 30-39 years of age. Participants reported working in collaboration on numerous aspects of BCS, and also reported the recommendation of starting screening at younger ages in contrast to existing guidelines. A higher percentage of participants recommended more clinical breast exams compared to mammograms or ultrasounds. Several perceived barriers in working with patients and lower physician comfort levels with aspects of BCS were identified. Graduate degree-holding physicians reported higher physician comfort levels, and lower screening and follow-up practice. Increased familiarity with screening guidelines resulted in higher screening and follow-up practice but also higher physician-patient barrier scores. Increased perceived importance in using guidelines correlated to higher screening and follow-up practice scores. Conclusion: The results of this study point to the potential utility and importance in understanding the demographic factors that influence physician beliefs and practices. Results also highlighted the need for evidence-based guidelines for physician education and culturally tailored materials to address communication barriers and physician comfort. Furthermore, when studying physician screening practices and beliefs, context-specific considerations, as well as interprofessional collaboration are essential to improve patient outcomes. Physicians hold a salient role in ensuring that patients have access to cancer screening. Focusing on this group provides a critical focal point in addressing disparities in breast cancer screening and improving outcomes amongst Chinese women.